11 Life's hard and then you die: PhD exploring end of life priorities for people experiencing homelessness within the United Kingdom. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Webb, Wendy A; Mitchell, Theresa; Snelling, Paul; Nyatanga, Brian
Abstract : Background: People experiencing homelessness often die young and without adequate support. In the UK, they fail to access palliative care services and their end-of-life priorities remain poorly understood. They are dying on the streets and in hostels without adequate support and, while there is ample literature surrounding the barriers to appropriate end of life care, the EoL priorities of people experiencing homelessness in the United Kingdom (UK) remain poorly understood. This study aims to bridge the gap in knowledge. Aims: To explore the end-of-life concerns, fears, preferences and priorities of a sample of people experiencing homelessness in the UK. Methods: This is an interpretive phenomenology. Data collected through semi-structured, audio-recorded, face-to-face interviews with 21 homeless participants in the UK were analysed iteratively using thematic analysis. Findings have been interpreted through the lens of Merleau-Ponty's philosophy. Results: Eight themes are reported: spiritual concerns; practical concerns; fear of needing care; fear of being forgotten; preference for dying suddenly; preference for being somewhere comfortable where people know me; prioritising autonomy and self-determination; and prioritising authenticity. Conclusion: Traditional palliative care services are possibly an unattractive resource for this population, so new approaches to care are required. Deeper understanding of the EoL concerns, fears, preferences and priorities of this marginalised population will support the development of accessible, culturally relevant, person-centred support for people experiencing homelessness with advanced ill-health in the UK. A strengths-based, trauma-informed, person-centred, collaborative 'compassionate community' approach to end of life care is recommended. Furthermore, the development of peer-support workers, trained in the principles of palliative care, should be actively encouraged and supported within the hostel as the hub of a compassionate palliative care community.